IL-9 and IL-24 biomarkers in the transcriptional signature of contact dermatitis to methylisothiazolinone - de Melo, Taynah Cohen; Sotto, Mirian Nacagami; Fernandes, Iara Grigoletto; De Sousa, Emanuella Sarmento Alho; Ferreira, Frederico Moraes; Simões, Gabriel Benevides; Ramos, Yasmim Álefe Leuzzi; Pincelli, Marcella Soares; Reis, Vitor Manuel Silva dos; Sato, Maria Notomi (Frontiers in Immunology, 2025)
IntroductionAllergic contact dermatitis (ACD) is a cutaneous inflammatory disorder mediated by allergen-specific memory T cells. Methylisothiazolinone (MI), a preservative widely used in industrial and cosmetic products and a component of Kathon CG, has led to a substantial rise in ACD cases. Despite increasing sensitization rates, the innate immune mechanisms and transcriptional responses induced by MI in the skin remain poorly understood.MethodsIndividuals with positive patch tests exclusively to MI were recruited at the Contact Dermatitis Clinic of Hospital das Clínicas (São Paulo). Participants were re-exposed to MI or saline, and skin biopsies were collected 48 hours later. Healthy MI-negative controls were also exposed to MI and saline. Histopathology and RNA-sequencing were performed. Differentially expressed genes (DEGs) were analyzed, and key findings were validated by qPCR and protein expression of IL-9 and IL-24.ResultsTwo distinct MI-responsive groups emerged among ACD patients:ACD-A (high responders): pronounced histopathology (spongiosis, microvesicles). ACD-B (low responders): milder reactions with absence of spongiosis. In ACD-A, MI exposure resulted in 1,588 upregulated and 2,090 downregulated genes compared to ACD-B. DEGs were enriched for innate immune and inflammatory pathways, including IL-24, IL-9, IL-13, and NTRK1 (upregulated), while IL-37 and IL-18 were downregulated. Compared to MI-negative ACD controls, ACD-A showed 1,169 upregulated and 321 downregulated genes. qPCR confirmed increased NTRK1 and IL-9 expression and reduced IL-18 levels. IL-9 and IL-24 protein levels were higher in the dermal layer of ACD-A.Discussion and ConclusionMI-sensitized individuals exhibit heterogeneous innate immune responses despite uniformly positive patch tests. IL-9, IL-24, and NTRK1 appear to play important roles in the heightened inflammatory response observed in high-responder individuals, while downregulation of IL-18 and IL-37 may contribute to impaired regulatory pathways. These findings highlight previously undescribed heterogeneity in MI-induced ACD and identify potential targets for better understanding disease pathogenesis.